2019
DOI: 10.1101/731604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Combinatorial MAP Code Dictates Polarized Microtubule Transport

Abstract: Many eukaryotic cells distribute their intracellular components through asymmetrically regulated active transport driven by molecular motors along microtubule tracks. While intrinsic and extrinsic regulation of motor activity exists, what governs the overall distribution of activated motor-cargo complexes within cells remains unclear. Here, we utilize in vitro reconstitution of purified motor proteins and non-enzymatic microtubule-associated proteins (MAPs) to demonstrate that these MAPs exhibit distinct influ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…However, the extent to which each MAP competes with MT motors can differ (Gumy et al, 2017). Since MAPs may be distributed differentially on the minus and plus end of a given MT (Qiang et al, 2018), movement of MT motors may vary depending on their location on the MT (Dixit et al, 2008; Monroy et al, 2019). As an example, the plus TIP complex that forms at the plus end of MTs may physically compete with MT motor binding, forcing the release of MT motors and associated cargo from the MT plus end (Akhmanova and Steinmetz, 2015).…”
Section: Physical Barriers To Diffusive and Active Cargo Movementmentioning
confidence: 99%
“…However, the extent to which each MAP competes with MT motors can differ (Gumy et al, 2017). Since MAPs may be distributed differentially on the minus and plus end of a given MT (Qiang et al, 2018), movement of MT motors may vary depending on their location on the MT (Dixit et al, 2008; Monroy et al, 2019). As an example, the plus TIP complex that forms at the plus end of MTs may physically compete with MT motor binding, forcing the release of MT motors and associated cargo from the MT plus end (Akhmanova and Steinmetz, 2015).…”
Section: Physical Barriers To Diffusive and Active Cargo Movementmentioning
confidence: 99%
“…Although the roles of DCLK1 and DCX in neurodevelopment have been phenotypically described in vivo, the molecular basis for these observations remains ill-defined. Prior studies have shown that DCLK1 and DCX may act as microtubule stabilizers, nucleators, and regulators of microtubule-based transport (29)(30)(31)(32)(33)(34)(35)(36). Dissecting the mechanisms by which DCLK1 binds to the microtubule can therefore provide insight into the microtubule-binding behaviors of other DCX family members and how they may be subverted in disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, upon an obstacle encounter, cargoes transported by dynein-dynactins often remain attached to the microtubule and undergo microtubule sliding 77 . Moreover, differential effects are exerted on kinesin and dynein motors by microtubule protein decoration 57 78 79 . DYRK1A appears to selectively modify the retrograde component due to changes in microtubule decoration and/or the regulation of active dynein motors in distal axonal loaded vesicles.…”
Section: Discussionmentioning
confidence: 99%